New environmentally friendly composite laminates with epoxidized linseed oil (ELO) and slate fiber fabrics. (15th March 2015) - Samper, M.D.; Petrucci, R.; Sánchez-Nacher, L.; Balart, R.; Kenny, J.M.
Abstract: This work focuses on the development of new composite laminates based on the use of epoxidized linseed oil (ELO) as matrix and reinforcement fabrics from slate fibers with different silane treatments. The curing behavior of the ELO resin is followed by differential scanning calorimetry (DSC) and the gelation is studied by oscillatory rheometry and gel-time. Composite laminates of ELO matrix and slate fabrics are manufactured by Resin Transfer Molding (RTM) and the mechanical properties of the composite laminates are tested in tensile, flexural and impact conditions. The effects of different silane coupling agents on fiber-matrix interface phenomena are studied by scanning electron microscopy (SEM). As in other siliceous fibers, silane treatment leads to improved mechanical performance but glycidyl silane treatment produces the optimum results as the interactions between silanized slate fiber and epoxidized linseed oil are remarkably improved as observed by scanning electron microscopy (SEM).